Bridging Group Divides: A Theoretical Overview of the "What" and "How" of Gateway Groups. (8th May 2019) - Love, Angelika; Levy, Aharon
Abstract: One of the most recent developments in the realm of intergroup relations is that of the gateway group notion. This conceptual framework addresses the potential of groups with multiple social backgrounds to play a role in the facilitation of positive intergroup relations between their distinct social counterparts (e.g., immigrants as a gateway between home and host countries). Given their shared identity with different social groups, people with multiple identities can potentially bridge the cleft between the two otherwise separate groups with which they are affiliated. In this article, we first provide a theoretical introduction to the gateway group notion and review preliminary experimental and social network‐based research on gateway groups' potential to improve intergroup relations. We then integrate this novel concept with the existing literature on intergroup contact and social categorization and discuss the potential social implications of gateway groups.